Best of Both Worlds: Synergistically Derived Material Properties via Additive Manufacturing of Nanocomposites. (29th July 2021) - Carrola, Mia; Asadi, Amir; Zhang, Han; Papageorgiou, Dimitrios G.; Bilotti, Emiliano; Koerner, Hilmar
Abstract: With an exponential rise in the popularity and availability of additive manufacturing (AM), a large focus has been directed toward research in this topic's movement, while trying to distinguish themselves from similar works by simply adding nanomaterials to their process. Though nanomaterials can add impressive properties to nanocomposites (NCs), there are expansive amounts of opportunities that are left unexplored by simply combining AM with NCs without discovering synergistic effects and novel emerging material properties that are not possible by each of these alone. Cooperative, evolving properties of NCs in AM can be investigated at the processing, morphological, and architectural levels. Each of these categories are studied as a function of the amplifying relationship between nanomaterials and AM, with each showing the systematically selected material and method to advance the material performance, explore emergent properties, as well as improve the AM process itself. Innovative, advanced materials are key to faster development cycles in disruptive technologies for bioengineering, defense, and transportation sectors. This is only possible by focusing on synergism and amplification within additive manufacturing of nanocomposites. Abstract : The combination of additive manufacturing with advanced nanocomposites creates new emerging material properties during processing, morphology evolution and novel functionalities with top level hierarchies that are dictated by print path topology. The synergistic, cooperative properties are key to unique capabilities that are not possible otherwise. This article takes a critical look at recent advances in this area and potential applications in automotive, civil engineering, biomedical, aerospace, and space.